Advancing Ethics and Policy for Healthy‐Volunteer Research through a Model‐Organism Framework. Issue 1 (22nd January 2019) - Fisher, Jill A.; Walker, Rebecca L.
ABSTRACT: Nonhuman animal research and phase I healthy‐volunteer clinical trials are both critical components of testing the safety of investigational drugs as part of the development of new pharmaceuticals. In addition, these types of research share important structural features, as both take place in confinement and both use subjects that are dissimilar to the target population. By mobilizing a model‐organism framework for phase I trials, we employ concepts and mechanisms typical to animal research to query gaps in the human subjects ethics and policy framework. By bringing these two research worlds together, we aim to illustrate how the model‐organism framework can enhance healthy volunteers' welfare during trials, improve research oversight, and more critically assess the science value of current phase I trials.